A handsome gift for the Apis - Malek, J. (ISIMU, 2016)
Bronze Apis bull No. 1879_332 in the Ashmolean Museum, Oxford, was dedicated by Harmakhoros, the brother of Pabasa, the chief steward of the God’s Wife of Amun, Nitocris I, sometime during the reign of Psammetichus I.